Pengaruh Kompetensi dan Keterampilan Kerja terhadap Kinerja Karyawan berbasis AMO (Ability, Motivation, Opportunity) pada Industri Rajasa Teknik - Kurniawan Wahyu Saputra; Wahyu Selamet Prihatin; Arrif Wahyudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This article explores inconsistencies in employee performance within small, project-oriented service sectors, where quality depends on daily tasks, punctuality, and adherence to procedures. Since skill development relies largely on informal workplace learning, differences in worker competencies often lead to rework, customer complaints, and safety issues. The study investigates how skills and competencies affect employee performance, illustrating how individual abilities translate into observable performance through the ability–motivation–opportunity (AMO) framework and experience-based learning. A qualitative case study at Rajasa Teknik included interviews and observations to examine project coordination, quality standards, and supervision practices. Results indicate that competencies and skills primarily influence ability, but sustained motivation- driven by realistic goals and fair feedback- along with ample opportunities such as smooth material flow, clear roles, and on-site decision support, enhance performance. The findings underline the importance of a cohesive work system (task division, quality control, communication), a consistent safety culture (K3), and straightforward, repetitive HR practices that facilitate tacit knowledge transfer into routines. Improvements suggested involve mapping core competencies, brief mentoring sessions, quality-focused standards, and evaluation systems to minimise service variation and promote sustainable performance in similar businesses. Overall, this research broadens the understanding of performance management in small enterprises and offers practical guidance for interventions.